MODEL PENDIDIKAN AKHLAK BERBASIS SIRAH NABAWIYAH BAGI GENERASI Z - Nadaiya Tur'rizki Siregar; Ainil Faidah; salwah lubis (Yayasan Baitul Hikmah al-Zain, 2026)
The rapid development of digital technology has faced unique moral challenges for Generation Z, such as easily distracted attention, a relative attitude toward right and wrong, and weakened integrity due to excessive exposure to uncontrolled virtual content. On the other hand, the Prophet's Sirah (Religious Life) offers a comprehensive model for developing noble character, emphasizing the balance between spiritual closeness, emotional stability, and mental resilience when faced with complex moral issues. Based on this, this study proposes a model of moral education based on the Prophet's Sirah, specifically tailored to the characteristics of Generation Z through digital, interactive, and project-based learning. The method used is a literature review and the preparation of a conceptual model, by analyzing the suitability of prophetic values ​​​​with the characteristics of Generation Z, including their tendency to seek authenticity in the digital world, think independently, and build solidarity networks in virtual communities. The conclusion of this study explains that the integration of Sirah Nabawiyah into adaptive and technology-based teaching strategies is seen as having strong potential to strengthen the moral immunity of Generation Z in the digital era, while encouraging the formation of an ethical and complete identity, sustainable, open, dynamic, and bringing change towards a better direction.